The association of the chromosome 9p21 locus on risk of coronary artery disease is not mediated via an effect on telomere length. (22nd September 2015) - Codd, V; van der Harst, P; Rafelt, S; Hall, AS; Samani, NJ
Abstract : Background: Recently, genome-wide association (GWA) studies of coronary artery disease (CAD) and myocardial infarction have identified a novel locus on chromosome 9p21.3, in which a common variant increases risk by 20–30% per copy of the allele. The mechanism by which the locus affects the risk of CAD is unclear and there is no correlation of the genotype at the locus with traditional cardiovascular risk factors. The region encompasses the genes coding for the cyclin-dependent kinase inhibitors p15ink4b and p16ink4a and a non-coding RNA, ANRIL . Although any function of ANRIL is not currently understood, the cyclin-dependent kinase inhibitors are regulators of the cell cycle and reduce cell proliferation and promote cellular senescence and apoptosis. As we and others have previously shown, an association between shorter telomere length, a marker of senescence and biological ageing and CAD risk, we investigated whether the 9p21.3 locus is associated with mean leucocyte telomere length and thus conveys the risk of CAD via a mechanism involving biological ageing. Methods: We measured telomere length in a subset (1487 CAD cases and 1430 National Blood Service control subjects) from the Wellcome Trust Case Control Consortium (WTCCC) GWA Study, which established the strong association of chromosome 9p21 with CAD. Mean leucocyte telomere length was measured using an established quantitative PCR technique, which expresses telomere length as a ratio of telomere repeat length (T) to a measured single copy gene (S). The association of genotype at the 9p21 locus (single nucleotide polymorphism rs1333049) with age and gender corrected telomere length was analysed. Results: The subset of cases and controls showed a strong association (p = 8.08 × 10 −11 ) of the locus with CAD as seen in the full WTCCC sample. Both case and control groups showed an age-related decrease in telomere length (decline in T/S ratio per year of −0.006 and −0.009, respectively, p<0.0001 for both cases and controls) and also exhibited a previously reported effect of gender, with women showing longer telomeres after accounting for age (+0.031 T/S ratio, p = 0.058 in cases and +0.033 T/S, p = 0.015 in controls). After adjusting for both age and gender there was a highly significant difference in mean telomere length between cases and controls of −0.29 in the T/S ratio (p<0.0001). However, despite observing the strong associations of both the chromosome 9p21 locus and shorter telomeres with the risk of CAD, we found no association of the 9p21 locus with telomere length (p = 0.56). Conclusions: We therefore conclude that the chromosome 9p21 locus does not affect the risk of CAD by a mechanism involving telomere length and premature biological ageing.